Analysis of Coupling Effect and Heavy Load of High-Temperature Stability of Asphalt Mixture - Lu Bai; Yong-sheng Zhang; Dai-song Luo (Advances in Materials Science and Engineering)
To study the variation in the high-temperature stability of asphalt mixtures under extreme high temperature and heavy load, rut tests and analyses were carried out with both the APA (asphalt pavement analyzer) test and CLWT (Chinese wheel load test). In this paper, the relationship model between the dynamic stability of asphalt mixtures and the temperature, load, and binder viscosity is established; this model provides a method for evaluating the temperature stability of asphalt mixtures under nonstandard temperature conditions. The results revealed that the dynamic viscosity of an SBS-modified asphalt binder showed an exponential relationship with temperatures varying from 55°C to 70°C. Under a temperature condition from 55°C to 70°C and a pressure of 0.7 MPa, the dynamic stability of the asphalt mixture increased linearly with increasing temperature. The dynamic stability of the asphalt mixture exhibited a temperature inflection point at 65°C, and the decay rate was increased. The APA test results, which were used to evaluate the anti-rutting performance of the asphalt mixture on the basis of the ratio of the rutting depth difference to action times from 6000 to 8000, showed a good correlation with the CLWT test results. With a high temperature of 65°C and the pressure increasing from 0.7 MPa to 1.3 MPa, the dynamic stability of the asphalt mixture exhibited exponential decay. The variation laws of dynamic stability with temperature, load, and asphalt binder viscosity were revealed by complex logarithmic variation.